PEMETAAN DISTRIBUSI KEJADIAN STREPTOCOCCUS SUIS DAN PENJUAL MAKANAN TRADISIONAL (LAWAR BARAK, SATE, DAN KOMOH) DI KOTA DENPASAR DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Listyawati, Ni Luh Putu; Subrata, Made (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 3 (2023): Desember 2023, 2023)
Balinese people have a tradition called mebat which is the process of preparing and cooking food, especially pork. One of the dishes that are often served when mebat is Lawar Barak, Sate, and Komoh. Consumption of undercooked food is a risk factor for contracting Streptococcus suis. Referring to the medical records of patients at Sanglah Hospital in 2014 – 2017, Denpasar City was ranked first as the highest case. The depiction Streptococcus suis and traditional food sellers (Lawar Barak, Sate, and Komoh) using GIS (Geographical Information System) is useful to determine the pattern of distribution of Streptococcus suis with the influencing factors in Denpasar City. This study was uses a descriptive quantitative design it describe the distribution of traditional food sellers (Lawar Barak, Sate, and Komoh) and the distribution of Streptococcus suis in Denpasar City using the Quantum GIS 3.24. The results showed that the highest cases of Streptococcus suis were in South Denpasar. This is supported by the high number of traditional food sellers (Lawar Barak, Sate, and Komoh) in that area, besides that sellers who have started selling since 2013 are also found in South Denpasar. It is recommended for further research to conduct laboratory tests on traditional foods (Lawar Barak, Sate, and Komoh) in Denpasar City. Keywords: Mapping, Streptococcus suis, Lawar Barak, Sate, Komoh